2017
DOI: 10.1186/s13584-017-0140-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug shortages in Israel: regulatory perspectives, challenges and solutions

Abstract: BackgroundPharmaceutical drug shortages (DSs) are a global problem which presents challenges to countries around the world. Shortages of pharmaceutical products may have a direct detrimental impact on public health and patients’ wellbeing by causing delayed, or even lack of, treatment. Moreover, DSs may force both patients and caregivers to use unfamiliar drugs, which could lead to medication errors. The objective of our study was to analyze DSs in Israel during the years 2013–2015, assessing their etiology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…Shortage of APIs affects many manufacturers worldwide, causing medicine shortages and leading to concerns with patient management [5,43,44]. Shortage of APIs was cited by the pharmacists as a reason given by suppliers when they were unable to supply orders of certain medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Shortage of APIs affects many manufacturers worldwide, causing medicine shortages and leading to concerns with patient management [5,43,44]. Shortage of APIs was cited by the pharmacists as a reason given by suppliers when they were unable to supply orders of certain medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the latest guidelines on managing shortages proposed by the ASHP, the TGA, and the EMA are based on risk assessment involving both manufacturing and distribution processes, as well as possible risks to patients when introducing therapeutic alternatives (Australian Government Department of Health, 2018; Fox and McLaughlin, 2018; European Medicines Agency (EMA) 2019a; European Medicines Agency (EMA) 2019b; European Medicines Agency (EMA) 2019a). The Israeli Ministry of Health conducts a protocol for healthcare professionals, managers, and importers to carry out risk assessment to propose solutions implemented nationally if no generic alternatives are available (Schwartzberg et al, 2017). According to the NHS' Department of Health and Social Care, performing risk assessment for joint procurement is recommended to avoid local duplication (Root, 2018; Government of the United Kingdom Department of Health and Social Care, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a Canadian report revealed that there were shortages of approximately 1000 medicinal products annually 8. The reports from Europe, Australia, Africa, China, Brazil, Fiji and Israel also indicated that medicines shortages were experienced on a regular basis and the trend has been growing rapidly 9–15…”
Section: Introductionmentioning
confidence: 99%